2020
DOI: 10.1002/joc.6866
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of projected changes of extreme precipitation indices in West Rapti River basin, Nepal under changing climate

Abstract: A better understanding of variations of extreme precipitation in space and time is essential for hydro-meteorological research and effective management of water resources. We used 11 extreme precipitation indices, some additional indices, and four seasonal precipitation based on daily precipitation data from 24 meteorologi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…This study uses a stage‐discharge relationship developed based on limited streamflow measurements. In general, qualified hydrologists only measure about 10–15 measurements in a year during low, mid, and high flows (Talchabhadel, Aryal, Kawaike, Yamanoi, & Nakagawa, 2021). Since the streamflow measurement during the extreme instances is challenging, extreme hourly streamflow has uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses a stage‐discharge relationship developed based on limited streamflow measurements. In general, qualified hydrologists only measure about 10–15 measurements in a year during low, mid, and high flows (Talchabhadel, Aryal, Kawaike, Yamanoi, & Nakagawa, 2021). Since the streamflow measurement during the extreme instances is challenging, extreme hourly streamflow has uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…Karki et al. (2017), Talchabhadel, Aryal, Kawaike, Yamanoi, and Nakagawa, 2021, and Bohlinger and Sorteberg (2018) reported that heavy precipitation related indices; maximum 1‐day precipitation amount (RX1day), maximum 5‐days precipitation amount (RX5day), and precipitation of days in >95th percentile (R95p), are rising significantly in lower hills of the western region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The proportional ratio‐based indices of these instances to total annual precipitation are similar to rain gauge observations. These ratio‐based indices inform the local nature of extreme precipitation events with respect to the PRCPTOT (Talchabhadel et al ., 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…However, the magnitude of alteration is uncertain (Allan & Soden, 2008;Allen & Ingram, 2002) and varies from region to region. Several studies attempt to unravel such precipitation alterations globally (Dore, 2005;Groisman et al, 1999), regionally (Klein-Tank et al, 2006), and at national (Bohlinger & Sorteberg, 2018;Kansakar et al, 2004;Talchabhadel et al, 2018) and basin scales (Dhaubanjar et al, 2020;Kaini et al, 2020;Talchabhadel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They developed four pathways, spanning a range of forcing in 2100 (2.6, 4.5, 6.0, and 8,5 watts per meter squared), but did not include any socioeconomic factors. Based on CMIP5, several studies (Dhaubanjar et al, 2020;Kadel et al, 2018;Kaini et al, 2020;Rajbhandari et al, 2016;Talchabhadel et al, 2020) are conducted on assessing precipitation variability during historical and future periods in Nepal. These studies project future scenarios across the river basins or the entire country using CMIP5 models.…”
Section: Introductionmentioning
confidence: 99%